MUTAGENIC AND GENOTOXIC EVALUATION OF MEDICINAL PLANT EUPHORBIA ROYLEANA LATEX TO FRESHWATER FISH CHANNA PUNCTATUS (BLOCH) - PRATIBHA SINGH,; ANURAG DABAS,; RASHMI SRIVASTAVA,; N.S. NAGPURE,; AJAY SINGH, (International Journal of Pharma and Bio Sciences, 2014)
The aim of present study was to evaluate the mutagenicity and genotoxicity induced due to medicinal plant Euphorbia royleana crude latex in fresh water fish Channa punctatus using micronucleus and single cell gel electrophoresis (SCGE) assays. Two sub-lethal concentration of crude latex were calculated using 24 hrs LC50 value and the fish specimens were exposed to these concentrations in a static system. Erythrocytes were sampled at the intervals of 24, 48, 72 and 96 hrs at the rate of five fish per interval for assessment of micronucleus induction and SCGE assay. Significant effects (P<0.05) for both concentration and time of exposure were observed in treated fish. Highest level of micronuclei induction in erythrocytes and DNA damage in the SCGE was at 96 hrs of exposure at all concentrations of crude latex. This study further confirmed that the micronucleus and SCGE assays are useful to determine potential genotoxicity of herbal formulation and might be appropriate as part of monitoring program.